Dietary Approaches to Attain Fish Health with Special Reference to their Immune System - Magrone, Thea; Russo, Matteo A.; Jirillo, Emilio (Current Pharmaceutical Design, 2018)
Fish despite their low collocation in the vertebrate phylum possess a complete immune system. In teleost fish both innate and adaptive immune responses have been described with melanomacrophage centers (MMCs) equivalent to mammalian germinal centers. Primary lymphoid organs are represented by the thymus and kidney, while spleen and mucosa-associated lymphoid tissues act as secondary lymphoid organs. Functions of either innate immune cells (e.g., macrophages and dendritic cells) or adaptive immune cells (T and B lymphocytes) will be described in detail, even including their products, such as cytokines and antibodies. In spite of a robust immune arsenal, fish are very much exposed to infectious agents (marine bacteria, parasites, fungi, and viruses) and, consequentially, mortality is very much enhanced especially in farmed fish. In fact, in aquaculture stressful events (overcrowding), microbial infections very frequently lead to a high rate of mortality. With the aim to reduce mortality of farmed fish through the reinforcement of their immune status the current trend is to administer natural products together with the conventional feed. Then, in the second part of the present review emphasis will be placed on a series of products, such as prebiotics, probiotics and synbiotics, β-glucans, vitamins, fatty acids and polyphenols all used to feed farmed fish. With special reference to polyphenols, results of our group using red grape extracts to feed farmed European sea bass will be illustrated. In particular, determination of cytokine production at intestinal and splenic levels, areas of MMCs and development of hepatopancreas will represent the main biomarkers considered. All together, our own data and those of current literature suggests that natural product administration to farmed fish for their beneficial effects may, in part, solve the problem of fish mortality in aquaculture, enhancing their immune responses.
Keywords: melanomacrophage centers